Mobile Marketing and its Effects on the Online Impulsive Purchasing Tendency - Bucht, Ellinor; Gillberg, Rebecka (2015)
Marketing is essential to influence consumers’ impulsive purchasing behavior and due to the fast development of both electronic and mobile commerce new ways of advertising have emerged. Mobile marketing is a channel that has the potential to be more effective than traditional mass media channels since it allows organizations to build personal relationships with their customers. The purpose of this thesis is to examine how different mobile marketing channels can influence consumers’ desire to purchase clothes impulsively online. This research is of descriptive and explanatory character and in order to answer the research purpose a quantitative study was conducted, where a questionnaire was randomly distributed to people in the city center of Luleå. The results suggest that individuals with a positive view towards SMS- and in-app advertising also react positively to online in-store promotion. Thus, the interactive effects between these promotional channels increase individuals’ general online impulsive purchasing tendency. Validerat; 20150612 (global_studentproject_submitter)